TEACHERS’ SPEECH TO STIMULATE STUDENTS IN LEARNING INTERACTION - Imam Suyitno; Martutik Martutik; Wevi Lutfitasari; Heni Dwi Arista (Universitas Negeri Makassar, 2021)
Many learning theories and studies on classroom discourse explain that teachers’ speech has an important role in determining student learning success. The teachers’ speech in teaching-learning interactions influences the activity and comfort of students’ learning. This study aimed to describe how the teachers’ speech stimulates students in learning interaction. This study used a qualitative approach to the type of classroom research. Participants in this study were 4 teachers who taught Indonesian, Mathematics, Science, and English at Mts. Islamiyah. Data of the study were the teachers’ speech and its context of stimulating students in learning interaction. The data collected through classroom observations and recording of teachers’ speech and the context of the speech. By qualitative analysis, this study found that the teachers’ speech at the beginning of learning, in the learning process, and at the end of learning has various types and functions depending on the speech context underlying the speech events in the classroom interaction. The speech context includes students as audiences, speech functions, learning material as speech topics, learning interactions as speech situations. The use of teachers’ speech was a learning strategy conducted by teachers to stimulate students motivated for learning.